Heterogeneity of intraepithelial lymphocytes in refractory sprue: potential implications of CD30 expression - Farstad, I N (Copyright 2002 by Gut, 2002)
Background: Refractory sprue is defined as primary or secondary failure to respond to a gluten free diet in patients with coeliac disease-like enteropathy and may signify cryptic or overt enteropathy associated T cell lymphoma. Aims: To study in detail jejunal morphology and immunophenotypes in patients with refractory sprue in the search for features that might be useful to predict prognosis. Patients: Seven patients are described, representing all such cases identified in our hospital over a 13 year period. Methods: Biopsy and/or surgical resection specimens were examined by morphology, immunohistochemistry, including enzymatic and immunofluorescent detection, and molecular biology. Results: All patients had phenotypically abnormal intraepithelial lymphocytes (IELs) that lacked CD8, T cell receptor αβ (or γδ), and/or expressed CD30 in addition to variable expression of the natural killer cell receptor CD94. A monoclonal T cell population was present in six cases, data from the seventh being inconclusive. Three patients had overt lymphoma with CD30+ tumour tissue intervening between intact mucosa that contained neoplastic IELs. Intriguingly, CD30+ IELs were observed both a long way away from, and in direct continuity with, the tumours in these patients. Such CD30+ cells were hardly detected in patients without tumours, two of which are in good health several years after the initial diagnosis. Conclusions: Our data suggest that abnormal IELs in patients with refractory sprue are phenotypically heterogeneous. CD30 expression by these cells may indicate a worse prognosis, including the occurrence of overt lymphoma.